Effects of heat treatment on Spin hamiltonian parameters of cr3+ions in natural pink sapphire - T. Kittiauchawal (2018)
© 2009 by World Scientific Publishing Co. Pte. Ltd. All rights reserved. The purpose of this research work is to investigate the eαects of heat treatment on spin Hamiltonian parameters of Cr3+ ions in natural pink sapphire sample. The pink sapphire were heated at diαerent temperatures of 1200, 1300, 1400, 1500 and 1600C in oxygen at-mosphere for 12 h, respectively. Electron Spin Resonance (ESR) spectra of pink sapphire samples before and after heat treatment were recorded in X-band frequency by mounting the crystal sample with the c-axis perpendicular to the applied magnetic eld direction. The spectra were recorded in the range of 0-180 degrees for every 15 degrees of rotation angle. It was found that, ve strong ESR absorption peaks at the magneticelds of 97, 163, 312, 519 and 724 mT were obtained. The magnetic elds of 163 and 519 mT cor-responding to Cr3+ ions replacing the Al3+ ions site of corundum structure (α-Al2O3), and those of 97, 312, and 724 mT were assigned to Fe3+ ions. Some conspicuous peaks of Cr3+ ion at various rotation angles were used to calculate the spin Hamiltonian param-eters by least-squarest method with the help of a computer program. The optimum spin Hamiltonian parameters of Cr3+ ions were then used to simulate the energy levels diagram of Cr3+ ions in sample before and after heat treatment.